A hydrophobic ammonia‐oxidizing archaeon of the Nitrosocosmicus clade isolated from coal tar‐contaminated sediment. Issue 6 (24th October 2016) - Jung, Man‐Young; Kim, Jong‐Geol; Sinninghe Damsté, Jaap S.; Rijpstra, W. Irene C.; Madsen, Eugene L.; Kim, So‐Jeong; Hong, Heeji; Si, Ok‐Ja; Kerou, Melina; Schleper, Christa; Rhee, Sung‐Keun
Summary: A wide diversity of ammonia‐oxidizing archaea (AOA) within the phylum Thaumarchaeota exists and plays a key role in the N cycle in a variety of habitats. In this study, we isolated and characterized an ammonia‐oxidizing archaeon, strain MY3, from a coal tar‐contaminated sediment. Phylogenetically, strain MY3 falls in clade ' Nitrosocosmicus ' of the thaumarchaeotal group I.1b. The cells of strain MY3 are large 'walnut‐like' cocci, divide by binary fission along a central cingulum, and form aggregates. Strain MY3 is mesophilic and neutrophilic. An assay of 13 C‐bicarbonate incorporation into archaeal membrane lipids indicated that strain MY3 is capable of autotrophy. In contrast to some other AOA, TCA cycle intermediates, i.e. pruvate, oxaloacetate and α‐ketoglutarate, did not affect the growth rates and yields of strain MY3. The attachment of cells of strain MY3 to XAD‐7 hydrophobic beads and to the adsorbent vermiculite demonstrated the potential of strain MY3 to form biofilms. The cell surface was confirmed to be hydrophobic by the extraction of strain MY3 from an aqueous medium with p ‐xylene. Our finding of a strong potential for surface attachment by strain MY3 may reflect an adaptation to the selective pressures in hydrophobic terrestrial environments.